Psychological and psycho-physical training as a factor of personal anxiety at students - Pichurin, V.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose : to test the hypothesis that the proposed content of the psychological and psycho-physical preparation of students of railway high schools in the physical education is effective in terms of reducing the high level of personal anxiety. Material : the study involved 120 students who had high levels of trait anxiety. Age of study participants was 17 - 19 years. Psychological diagnostics level of personal anxiety in students was conducted using a scale assessing the level of reactive and personal anxiety Ch.Spilberger. Results : the use in psychological and psycho-physical training in the classroom for physical education for men (significant sports - athletics and powerlifting) and girls (aerobics and Sahaja Yoga) significantly influenced the decline in their personal anxiety. Conclusions : It is recommended that training on physical education to carry out the following structure. Preparatory part of the class - 10 minutes. Basically - 75 minutes. Of these, 25 minutes - to solve the traditional problems of physical education students to build their motor skills and the development of physical qualities. 20 minutes - was given to the students to perform specific exercise. 30 minutes devoted to the main part of a busy professional significant sport. The final part - 5 minutes.